Project Management for Instructional Designers - Clements, Geri; Drysdale, Jeffery; Francis, Jenifer; Open Textbook Library (Open Textbook Library, 2012)
Project Management for Instructional Designers (PM4ID) is - as the name suggests - a book about project management tailored specifically for instructional designers. This book is a revise / remix of a pre-existing, openly licensed project management textbook which was donated to the commons by a benefactor that desires to be attributed as Anonymous. PM4ID includes many new features and improvements to the original book, including: Alignment of book chapters with the PMBOK, which supports readers in preparing for the Project Management Professional certification, A series of video cases of project managers working in the instructional design area, integrated into every chapter, Multiple versions of the book, including HTML, PDF, ePub, Kindle, and a text-to-speech mp3 audio version of the book, New examples written specifically for readers coming from the instructional design perspective, and more.
Chapter 1: Introduction to Project Management -- Chapter 2: Project Profiling -- Chapter 3: Project Phases and Organization -- Chapter 4: Understanding and Meeting Client Expectations -- Chapter 5: Working with People on Projects -- Chapter 6: Communication Technologies -- Chapter 7: Starting a Project -- Chapter 8: Project Time Management -- Chapter 9: Costs and Procurement -- Chapter 10: Managing Project Quality -- Chapter 11: Defining Risk -- Chapter 12: Project Closure
In English.
Description based on print resource
Keywords: Education -- Textbooks; General education -- Textbooks